Spatiotemporal denudation rates of the Swabian Alb escarpment (southwestern Germany) dominated by anthropogenic impact, lithology, and base-level lowering - M. Schaller; M. Schaller; D. Peifer; A. B. Neely; T. Bernard; C. Glotzbach; A. R. Beer; T. A. Ehlers (Earth Surface Dynamics, 2025)
Surface denudation rates, a composite of physical erosion and chemical weathering, are governed by the tectonic, lithologic, climatic, and biotic conditions of a landscape and anthropogenic disturbances. Quantifying rates and disentangling their causes is challenging but important for understanding and predicting landscape evolution over space and time. In this study, we focus on a low-relief and mixed-lithology mountain range (Swabian Alb, southwestern Germany), whose 200–400 m high escarpment and foreland drain to the Neckar River to the north and whose plateau drains into the Danube River to the southeast. These two drainage systems are subjected to similar uplift rates and climate and biotic conditions but contain different lithologies, base levels, and topography. We calculate decadal-timescale chemical weathering and physical erosion rates based on 43 locations with suspended and dissolved river load measurements and compare them to published longer-term rates (e.g., denudation, incision, uplift).